IMPLEMENTASI BAHASA JURNALISTIK DALAM PENULISAN SOFT NEWS DI WEBSITE TRIBUNNEWS BOGOR - Yuningsih, Asri; Bachtiar, Willy; Latif, Alfa Taufan (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2025)
The development of online media in the digital era has driven significant changes in journalistic practices, including the use of journalistic language. This study aims to describe and analyze the implementation of journalistic language in the writing of soft news articles on the Tribunnews Bogor website. The research approach employed is qualitative, using an analytical method based on Sumadirian's (2016) theory, which emphasizes simplicity, accuracy, word economy, and emotional appeal. Data collection was conducted through in-depth interviews with journalists who also serve as editors at Tribunnews Bogor, as well as through non-participatory observation. The results of the study show that the soft news writing process at Tribunnews Bogor is carried out systematically, starting from the selection of topics that contain elements of human interest, novelty, and proximity, to the presentation of news in a narrative style. The use of journalistic language is reflected in simple, straightforward, and efficient sentence structures, as well as in the selection of communicative and easily understood diction. In addition, the application of the journalistic elements of 5W+1H, the use of direct quotations, and the choice of a human-centered perspective are key characteristics of soft news writing in Tribunnews Bogor. Key words: Journalistic Language, Soft News, Tribunnews Bogor